Walking Through Pictures : Hommage aan Guy Leclercq. - Klewais, Willem; Academie voor Beeldende Kunsten, Anderlecht (Anderlecht : Willem Klewais, 2005)
Begerem, Tita ; Bertrand, Joannes ; Bogaert, Wien ; Bogaerts, Diane ; Borrezee, Suzanne ; Bruylandt, André ; Cannoodt, Mark ; Carpay, Mut ; Catala, Jean ; Coenegrachts, Sabine ; et al.
Academie voor Beeldende Kunsten, Anderlecht, 2005
kunstcatalogus